The three worlds of multilevel democracy: Local linkages, civil society and the development of the modern state - SELLERS, Jefferey (Institutional Knowledge at Singapore Management University, 2015)
The Three Worlds of MultilevelDemocracydevelops and applies a novel theory of democratic governance. This theory incorporates micro-level patternsof governance and civic organization at the local scale into a comparative macro-analysisof national democratic institutions. Institutionsand politics at the micro-level of cities and communities provide the basis fora new perspective on national state-society relations. We demonstrate how these local patterns havedeveloped through historical processes that were often distinct from those thatgave rise to national democratic institutions, and analyze how they have shapeddemocratic institutions at the national level. These local patterns continue to account for significant cross-nationalcontrasts in the quality of democracy and the performance of policy.